Exploitation of second-and fourth-order PDEs to improve Lossy compression of noisy images. (1st April 2023) - Welba, Colince; Simo, Thierry; Noura, Alexendre; Ntsama, Pascal Eloundou; Ele, Pierre
Abstract: This paper presents a lossy compression method for noisy images. The main contributions in this paper are: improve the performance of noisy image compression algorithms by using partial differential equations (PDEs) as an image preprocessing filter and show that it is more advantageous to apply a restoration filter before compressing noise images. Method : The preprocessing filter is applied to the noisy image first. A comparing of the obtained outcomes with those in the scientific literature devoted to the restoration of noisy images is performed. The filtered image is then submitted to a compression algorithm. The compression algorithm employed is a hybrid of the following: DWT + SPIHT + HUFFMAN. Results : The simulation results demonstrate that the suggested technique is as efficient as approaches described in the scientific literature for picture compression and/or image restoration.